2016
DOI: 10.1098/rsbl.2016.0228
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional body sizes but typical trophic structure in a Pleistocene food web

Abstract: In this study, we focused on the exceptionally large mammals inhabiting the Americas during the Quaternary period and the paramount role of body size in species ecology. We evaluated two main features of Pleistocene food webs: the relationship between body size and (i) trophic position and (ii) vulnerability to predation. Despite the large range of species sizes, we found a hump-shaped relationship between trophic position and body size. We also found a negative trend in species vulnerability similar to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This trophic classification recognizes seven categories: Predatory carnivores, browsing carnivores, herbivorous omnivores, herbivores, herbivores on rock, rubble or coral substrates, herbivores on plant or algal substrates, and suspension feeders (Table 1). Each species in the Malacolog database was assigned to one of the above-described categories combining them on the general categories of Carnivore-Non Carnivore (Arim et al 2007b(Arim et al , 2010Segura et al 2016).…”
Section: Dietary Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…This trophic classification recognizes seven categories: Predatory carnivores, browsing carnivores, herbivorous omnivores, herbivores, herbivores on rock, rubble or coral substrates, herbivores on plant or algal substrates, and suspension feeders (Table 1). Each species in the Malacolog database was assigned to one of the above-described categories combining them on the general categories of Carnivore-Non Carnivore (Arim et al 2007b(Arim et al , 2010Segura et al 2016).…”
Section: Dietary Informationmentioning
confidence: 99%
“…When the phylogenetic, temporal or spatial scales are large enough, a hump-shaped relationship between trophic position and body size is expected (Arim et al 2007a) and reported (Burness et al 2001(Burness et al , 2016Segura et al 2015aSegura et al , 2016. Despite this, there have been numerous reports of positive relationships within taxonomic groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of body size to metabolism also plays a central role in the study of evolution and life histories of extinct species. In particular, Cope’s rule (Cope 1904), in which over evolutionary time the body size of clades increased by orders of magnitude (Alroy 1998; Smith et al 2010; Evans et al 2012; Benson et al 2014), is thought to be driven by interactions of ecological process and abiotic forcing (Raia et al 2012; Saarinen et al 2014; Segura et al 2016). However, the body size increase also may be controlled by intrinsic biological factors (Sookias et al 2012) that are limited by the allometric relationships of mass to metabolism and generation time, which in turn set the rate of gene mutation (Okie et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of body size to metabolism also plays a central role in the study of evolution and life histories of extinct species. In particular, Cope's rule (Cope 1904), in which over evolutionary time the body size of clades increased by orders of magnitude (Alroy 1998;Benson et al 2014;Evans et al 2012;Smith et al 2010), is thought to be driven by interactions of ecological process and abiotic forcing (Raia et al 2012;Saarinen et al 2014;Segura et al 2016). However, the body size increase also may be controlled by intrinsic biological factors (Sookias et al 2012) that are limited by the allometric relationships of mass to metabolism and generation time, which in turn set the rate of gene mutation (Okie et al 2013).…”
Section: Introductionmentioning
confidence: 99%